ANCAMAN DISKRIMINASI MINORITAS DAN HILANGNYA MULTIKULTURALISME DI INDONESIA: STUDI KASUS PENUTUPAN GKI YASMIN BOGOR - Budi Chrismanto Sirait (Program Magister Ilmu Politik, Universitas Diponegoro, 2019)
This article is based on research in Gereja Kristen Indonesia (GKI, Indoensian Christian Chruch) Yasmin Bogor as a case study. It has been years for the community to struggle for gaining permission to legally build the church. Court has decided to allow the community to use the building for religius activities. However, practically, the court's decision cannot be implemented because there was pressure for some parties, including from the local government, to refuse the operation of the church. The study is aimed to identify the dynamics and difficulties of being minority in a nation-state, called Indonesia. This lengthens the list of acts of intolerance and violence on minority within a democratic government, in which majority is still preferred. There is a celar need for changing the mindset of the state and society to resolve conflict based on religious belief, to enable equality in economy, politics and religious life.